Poverty, Vulnerability, and Household Coping Strategies during the 2015-16 Recession in Belarus - Bornukova, Kateryna (World Bank, Washington, DC, 2019)
This paper examines the impact of the recent recession in Belarus on poverty and broader measures of household welfare and compares the recent recession episode to previous economic crises in Belarus. The paper constructs a measure of vulnerability to poverty, based on an estimated probability of falling below the national poverty threshold not exceeding 10 percent, which is estimated for each year of the household survey data between 2014 and 2017. The analysis finds that the recession of 2014-16 was qualitatively different from earlier recent crisis episodes (2008-09 and 2010-11) in that it affected low-income households to a much greater extent, and the negative welfare effects lingered. The paper also documents that although the recession did not result in a substantial increase in absolute poverty by the official definition, it led to a considerable increase in the share of households that are vulnerable to poverty. The greater degree of vulnerability is also evident from the growing share of the population that faced a risk of poverty within a year (going in and out of poverty). Household types for which the impact of the recession was most pronounced are households with multiple children, single-parent households, residents of rural areas, as well as those who were not employed, partly employed, or low-skilled employees. Coping strategies that were employed by the population were largely related to reducing expenditures and, among vulnerable households, food expenditures in particular, as well as drawing down on their savings.